2020
DOI: 10.3390/ijgi9010043
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-Based Construction of Quadrilateral Table Cartograms

Abstract: A quadrilateral table cartogram is a rectangle-shaped figure that visualizes table-form data; quadrilateral cells in a table cartogram are transformed to express the magnitude of positive weights by their areas, while maintaining the adjacency of cells in the original table. However, the previous construction method is difficult to implement because it consists of multiple operations that do not have a unique solution and require complex settings to obtain the desired outputs. In this article, we propose a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Changes to these values might be invisible (yielding a Confuser ) if the change is small or the cells are not labeled with their corresponding value. This suggests that, like both geographic cartograms [NK16] and tree maps [Fri94], TACOs are more effective when used in conjunction with a secondary visual encoding, such as color or text, as it facilitates easier value retrieval than simply using area alone [IL20]. We argue that, given the low accuracy of the perceptual system for understanding numeric values through area [Mac86], that value retrieval hinges on the presence of secondary annotations, and possesses a Confuser otherwise.…”
Section: Algebraic Visualization Analysis Of the Table Cartogrammentioning
confidence: 99%
See 1 more Smart Citation
“…Changes to these values might be invisible (yielding a Confuser ) if the change is small or the cells are not labeled with their corresponding value. This suggests that, like both geographic cartograms [NK16] and tree maps [Fri94], TACOs are more effective when used in conjunction with a secondary visual encoding, such as color or text, as it facilitates easier value retrieval than simply using area alone [IL20]. We argue that, given the low accuracy of the perceptual system for understanding numeric values through area [Mac86], that value retrieval hinges on the presence of secondary annotations, and possesses a Confuser otherwise.…”
Section: Algebraic Visualization Analysis Of the Table Cartogrammentioning
confidence: 99%
“…One way to address this failure mode is to impose additional constraints-such as by minimizing bearing angle differenceswhich causes there to be a single "correct" layout [IL20]. While these criteria can yield more rectangular displays, their selection is arbitrary and an artifact only of designers' preferences, an ambi- guity which may in turn hold another Hallucinator.…”
Section: Algebraic Visualization Analysis Of the Table Cartogrammentioning
confidence: 99%
“…The visual effect is that of a shaded matrix that has been "area-ed" rather than merely colored. A given dataset can produce multiple equally accurate table cartograms because the problem is under-constrained [3].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrate that every dataset admits a table cartogram by providing a constructive computational geometry algorithm. Subsequent work by Inoue and Li [3,4] found that it was more effective to generate them through mathematical optimization procedures. Unfortunately, both approaches are capable of generating only a single solution for a given dataset, which precludes the aesthetic control of the output or design-focused exploration of the solution space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation